(599) Theoretical Problems of Industrial Planning (parts):The Instruments of Industrial Planning) المشكلات النظرية للتخطيط الصناعي (عدة أجزاء) - Linsel, H.; Sack, K. (INP, 2024)
This section of the book addresses the instruments of industrial planning, beginning with an introduction that highlights the importance of these tools in achieving economic goals. The first section discusses the framework of national economic plans, explaining how these plans are organized to achieve economic balance. Next, the book explores the system of balances and indicators, which serves as a crucial tool for evaluating economic performance. It also delves into the concept of interlacing balances and how they interact with each other in industrial planning. Finally, the book reviews the practical use of interlacing balances, illustrating how these tools can be applied in reality to achieve effective results.